MOTOR ALALIYALÍ BALALARDA KOMMUNIKATIV KÓNLIKPELERDIŃ QÁLIPLESIWI - Ajimova, Zuxra Ganibaevna (SCIENCE and SOCIETY, 2026)
The article examines the problem of forming communicative competence in children with motor alalia. The features of the speech and communicative development of this category of children are revealed, and methods of logopedic influence aimed at developing verbal and nonverbal means of communication are described. The results of the correctional work, confirming the effectiveness of a comprehensive approach to the formation of communicative competence, are presented.